Enhancing Security Mechanisms for Healthcare Informatics Using Ubiquitous Cloud - Kumar, Dinesh; Smys, S. (Journal of Ubiquitous Computing and Communication Technologies, 2020)
The most vital chores of the health care is the proper attention and sharing of the information’s about the patients record maintained whenever it is needed. The failure in proper maintenance of the patient’s particulars and proper sharing of information’s when required would lead to loss of privacy and reliability resulting in the inert and severe effects on the particulars of the patients as well as their lives respectively. So securing of the health care particulars in electronic form becomes a very important necessity nowadays. The constant monitoring of the centralized storage of health records that are prone to security threats are very difficult. So the paper puts forward a block chain technology to safeguard the reliability of the information’s stored and utilizes the digital signature with authentication to protect the private information’s in the patient’s record developing a model utilizing the cloud that enables the authenticity and the reliability of the information. The model put forth in the paper was examined and compared with the traditional techniques used for storing the medical records, on the terms of reply time, along with the cost of storing and retrieving.